External factors effecting the efficiency of takaful operators and conventional life insurers - Yakob, Rubayah (2014)
The success of insurers as well as takaful operators is highly reliant on their financial management efficiency. Two functions that are vital to the financial management are risk and investment management. These 2 functions are said to be very important because it manages key elements in the operation of the insurer/takaful operator - risk, return and capital. The changes in consumer preferences and the risk of insolvency has created a strong impetus to the players in the industry to improve the efficiency of their financial management in order to survive and compete in this business. However, the efficiency of financial management depends on many other factors including macroeconomic factors and firm-specific characteristics. Thus, the main objective of this study is to identify the determinants of the efficiency of financial management, to be precise, efficiency of risk and investment management but merely focus on firmspecific characteristics that are not within the control of managers that is known as external factors. The sample of this study involves 20 firms consisting of 7 life insurers, 9 composite insurers and 4 takaful operators that consistently present in Malaysia throughout the period 2003 to 2007. The data is limited to life insurance, family takaful and investment-linked business. The dependent variable in this study is the efficiency score of risk and investment management, while the external/independent variables consist of operating systems (takaful operators versus conventional insurers), organizational form (mutual versus stock), consumer preference towards the investment-linked policy and size. The two-stage regression method is used in achieving the objective of this study. In the first stage, slack-based measure – data envelopment analysis (SBM-DEA) is applied in order to obtain the efficiency score of risk and investment management of each insurer/takaful operator. In the second stage, the efficiency scores calculated from the first stage is regressed with independent variables by using Tobit analysis. The result reveals that the mutual company (owned by the policyholders – non profit oriented) is having better risk management performance than their stock (owned by the shareholders – profit oriented) counterparts in which the mutual company is also the takaful operator in this study. Indirectly, this indicates that the takaful operators are more efficient than conventional insurance companies in terms of risk management. In addition, the result also confirms that the large insurers/takaful operators are more efficient in terms of risk management. However, consumer preference is found to be insignificantly correlated with the efficiency of risk management. In contrast with risk management, size and organizational form is not the indicator of the investment management efficiency, but consumer preference towards the investment-linked policies is significantly and positively associated with investment management efficiency. From these results, the insurer/takaful operator is expected to enhance their risk management practices and investment strategies to ensure their role as risk bearer, financial service provider and intermediary can be preserved as well as accomplishing the requirements of their stakeholders. In response, the government should provide the infrastructure to support the improvement of financial management efficiency among insurers/takaful operator, mainly in regards of takaful operator’s licenses, merger and acquisition, and the Syariah compliance investment mechanisms.